THE EFFECT OF THE CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH ON STUDENTS' NUMERACY ABILITY - Shafirah; Ayu Tsurayya (Jurnal Math-UMB.EDU, 2025)
This study aims to determine the effect of the Culturally Responsive Teaching (CRT) approach on learners’ numeracy ability. This research is a quantitative study with a true-experimental approach with a pretest-posttest control group design. It involves measuring learners' numeracy ability before and after treatment through written tests. The data were analyzed using the t-statistical test to determine the significance of the difference in numeracy ability between the experimental and control groups. The results showed that learners who participated in learning with the CRT approach experienced a more significant improvement in numeracy ability compared to the control group. The findings support the application of a culturally-based approach to improve numeracy ability in a contextually and innovatively. Keywords: Culturally Responsive Teaching, Numeracy Ability, Mathematics Learning